(untitled) (Texas Journal of Medical Science, 2023)
In medicine, the role of medical images in the field of radiology is very important. Accuracy of medical images and high quality of images are very important to the attending physician in making an accurate diagnosis of the patient. Processing, storage, transformation of medical images, conversion from analog to digital form.